The Pandemic as a Catalyst for Digital Pathology Adoption as an LDT. (9th November 2022) - Smith, Geoffrey; Raiff, Ross; Badve, Sunil; Krasinskas, Alyssa; Roback, John
Abstract: Whole-slide images (WSI) are the basis for the application of artificial intelligence/machine learning and other informatics methods to histological diagnosis and will further blur the line separating anatomic and clinical pathology. FDA classified WSI systems for primary diagnosis as class III (highest risk) medical devices until 2017. This discouraged anatomic pathology laboratories at risk-averse domestic institutions like mine from investing in these digital pathology (DP) platforms. In 2017, FDA downgraded WSI to class II (moderate risk) when they de-novo approved a system marketed by Philips. We were not interested in that system at my institution, but the downgrade caused us to reset our perception of the risk of validating a RUO system for primary diagnosis. Cost remained a barrier. In April 2020, FDA issued temporary guidance stating they would not enforce premarket approval of WSI systems to facilitate pathologists working remotely during the SARS-CoV-2 pandemic. The guidance included a statement that "laboratories and hospitals consider performing a validation study." In January 2021, FDA proposed making the temporary non-enforcement guidance permanent. So, in a little more than three years, WSI for primary diagnosis had gone from class III to exempted from pre-market approval! This nicely aligned the approval framework for WSI with the approval framework for our conventional optical microscopes, which are statutorily exempted from approval, and further reset our perception of risk. In April 2021, FDA withdrew the proposal to make non-enforcement permanent, but the temporary non-enforcement guidance is still in effect at the time of writing. Amid all this FDA activity, the College of American Pathologists updated and reissued their consensus guidelines for validating WSI systems for diagnostic purposes in March 2021. The narrative mentions the FDA's recent approval of a few WSI systems and anticipates more, but the expert panel recommendations do not include any related to the approval status of systems. The reissue of this document reminded us that, as clinical laboratorians, we are capable of safely validating WSI as a laboratory-developed test and are supported in doing so by consensus guidelines from one of our leading professional organizations. In early 2021 we committed to funding a DP initiative to make WSI part of our routine histological process for 10% of our anatomic pathology cases. The initial capital investment is 1.5M. When realized, the microscope slides for designated pathology services will be transported directly from the cover slipper to a slide scanner and electronically distributed to pathologists using a clinical-grade image management system that we share with our radiology department. We made the decision to fund this in the context of the regulatory (decreased perception of risk), sociological (demand for remote telepathology), and technological (availability of scalable WSI systems) changes that occurred during the pandemic.